PROBLEMATIKA GENDER DALAM PERSPEKTIF DAKWAH - Siti Nurul Yaqinah (Universitas Islam Negeri (UIN) Mataram, 2016)
Islam insists that human beings are created as God’s caliph in the world. The definition of caliph as a substitute, functions as confirmation and responsibility to human beings to do their duties in the world. This is not only for men but also women. The messages of Al-Quran to human are like life lantern providing light and enlightening human life from the grief of darkness, but the messages are frequently distorted by various human interest. Supposing we say the issues related to gender usually become the problem of gender inequality, either male or female. The term ‘gender’ literally means sex distinguishing all aspects between male and female in terms of action, attitude, effort and activity. Indeed, Islam truly defies against the discrimination in all aspects including discrimination to female because the main purpose of Islam come to against all form of discrimination, especially to woman. Islam is as guidance to all human being without any difference between man and woman. The current discrimination to woman should be omitted because man and woman complete each other as the manifestation of God’s creation in the world.